School Safety or School Criminalization? The Typical day of A School Resource Officer in the United States - Higgins, Ethan M (The British journal of criminology, 2022)
School resource officers (SROs) have become increasingly common in schools in the United States and this growth of police in schools has taken place as part of a trend of school criminalization. In a school criminalization framework, scholars have focused on physical security measures and punitive outcomes for students, however, the subtler dimensions have been less explored. We draw on 26 interviews where SROs were asked to detail their typical day to investigate whether, and how, SROs criminalize school spaces through routine tasks. In spite of the multi-faceted roles of the SRO, the SROs in this study framed a typical day through a crime control logic where school spaces are criminogenic hotspots and the student body is ripe with potential offenders.